Continuous Training and Wages – An Empirical Analysis Using a Comparison-group Approach - Katja Görlitz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Using German linked employer-employee data, this paper investigates the impact of on-the-job training on wages. The applied estimation technique was first introduced by Leuven and Oosterbeek (2008). The idea is to compare wages of employees who intended to participate in training but did not do so because of a random event with wages of training participants. The estimated wage returns are statistically insignificant. Furthermore, the decision to participate in training is associated with sizeable selection effects. On average, participants have a wage advantage of more than 4% compared to non-participants. – – Basierend auf den Daten eines deutschen Linked-Employer-Employee Datensatzes untersucht dieses Papier den Effekt von Weiterbildung auf die Lohnentwicklung von Beschäftigten. Die empirische Methode basiert auf dem Ansatz von Leuven und Oosterbeek (2008). Die Idee ist, Löhne von Teilnehmern mit den Löhnen einer Gruppe von Nichtteilnehmern zu vergleichen, die eine Weiterbildung fest geplant hatte, diese aber aus exogenem Grund absagen musste. Die Schätzungen liefern einen insignifikanten Effekt. Des Weiteren kann gezeigt werden, dass die Entscheidung, an Weiterbildung teilzunehmen, mit großen Selektionsverzerrungen einhergeht. Teilnehmer haben einen durchschnittlichen Lohnvorsprung von mindestens 4% im Vergleich zu Nichtteilnehmern.
Keywords: J24; J31; 330; continuous training; wage returns; selection effect